Coupling metabolic footprinting and flux balance analysis to predict how single gene knockouts perturb microbial metabolism - Correia, Gonçalo dos Santos, 1989- (2013)
Tese de mestrado. Biologia (Bioinformática e Biologia Computacional). Universidade de Lisboa, Faculdade de Ciências, 2012